Productivity and Nutrient Dynamic of Legume in a Maize-legume Cropping System are Influenced by Biomulches Under No-tillage System - Dey, Joy Kumar; Saren, Binoy Kumar; Debnath, Ashim; Gudade, Bharat Arjun; Singh, Satyapriya; Kumar, Amit; Palai, Jnana Bharati; Gaber, Ahmed; Hossain, Akbar (International journal of plant production, 2022)
Agronomic measures to conserve the residual soil moisture are very suitable for the dry area because of their very low cost and ability to reduce soil erosion. The region where after the harvest of rainy season crops, lack of sufficient soil moisture accessibility limits the cultivation of dry season crops. A technique like retaining crop residues and weed biomass on the soil surface along with zero tillage initiates the process that leads to improve soil quality and overall enhancement of resource use efficiency. The study was carried out to find out the productivity and nutrient dynamic of rabi legume in maize-legume cropping system under residual moisture conditions with bio-mulches and no-tillage. It will be helpful to develop sustainable and resource-efficient cropping system pattern for the region. A field trial was conducted for consecutive two years (2017–18 and 2018–19) at the dry region of West Bengal, India to assess the bio-mulches under the no-tillage condition on soil properties, productivity and nutrient uptake of legumes under Maize-legume cropping systems. From the experiment, it was revealed that the maize-lathyrus cropping system in combination with bio-mulching i.e. in-situ maize stalk mulch (MSM) + Paddy straw (5 t ha – 1 ) is the best efficient maize-based cropping systems and soil moisture conservation measures for improving soil fertility, crop yield and nutrient uptake in the rainfed dry region. Therefore, it could be concluded that the growing of legume pulses under different cropping systems along with no-tillage not only will improve the soil fertility status but also will increase the production and cropping intensity. This type of study could also be done under crops like winter oilseeds, cereals, tuber crops under different agro-climatic situations with locally available bio-mulches.